Research on Capacity Optimization of Wind Solar Complementary Hybrid Energy Storage System - Chen, Jiashuo (Transactions on Environment, Energy and Earth Sciences, 2026)
With the "dual carbon" aim being widely promoted, there is an urgent need to promote the sustainable development of wind solar complementary power stations (WSCPS). Therefore, this article proposes an optimization model for wind solar complementary hybrid energy storage system. Firstly, establish a mathematical model for the hybrid energy storage system (HESS) and propose a power allocation strategy for the HESS; Then, with the energy storage capacity configuration parameters as optimization variables and the minimum lifecycle cost of HESS in WSCPS as the optimization objective, Cauchy mutation adaptive particle swarm optimization (CMAPSO) is used to solve the actual case study; Finally, the Cauchy mutation adaptive particle swarm optimization (CMAPSO) used in this study is compared with particle swarm optimization (PSO) and adaptive inertia weight particle swarm optimization ( AIWPSO ). It can be seen from the comparison results that the optimal values of CMAPSO and AIWPSO are 64.3 % and 53.1 % lower than those of PSO, respectively. The optimization ability of CMAPSO is stronger. Comparing the mean and variance, it can also be seen that the optimization accuracy of CMAPSO algorithm is higher and relatively stable, the usefulness and superiority of the suggested scheme and algorithm were demonstrated.